Pomegranate Peels as Biosorbent Material to Remove Heavy Metal Ions from Industerial Wastewater - Shartooh, S.; Al-Azzawi, M.; Al-Hiyaly, S. (Iraqi Journal of Science, 2024)
Pomegranate peels were used to remove zinc, chromium and nickel from industrial wastewater. Three forms of these peels (fresh, dried small pieces and powder) were tested under some environmental factors such as pH, temperature and contact time.The obtained results showed that these peels are capable of removing zinc, chromium and nickel ions at significant capacities. The powder of the peels had the highest capability in bioremoving all zinc, chromium and nickel ions while dried peels had the lowest capacity again for all metals under test. However, the highest capacities were found in a sequence of chromium, nickel and zinc. Furthermore, all these data were significantly (LSD peel forms = 2.761 mg/l, LSD metal ions = 1.756 mg/l) varied.In case of chromium, these figures were 69.7 ± 0.9 mg/l, 58.0 ± 2.4 mg/l and 49.7 ± 0.5 mg/l for powder, fresh and dried peels respectively. Regarding nickel ions, the data were 58.7 ± 1.1 mg/l for peel powder, 50.7 ± 2.0 mg/l for fresh peel and 42.0 ± 1.2 mg/l for dry peel. While for zinc ions, the biosorption capacity was 48.4 ± 2.2 mg/l, 39.4 ± 0.8 mg/l and 32.0 ± 1.6 mg/l for powder, fresh and dry peels respectively.However, some examined factors were found to have significant impacts upon bioremoval capacity of pomegranate peels such as pH, temperature, and contact time where best biosorption capacities were found at pH 4, with temperature 50 Cº and contact time of 1 hour.Regarding pH, the highest bioremoval ability was found at pH 4 for all heavy metals, but with the sequence of Cr, Ni, and Zn and the data were 68.1 ± 1.5 mg/l, 56.0 ± 0.5 mg/l and 47.88 ± 1.21 mg/l respectively. Similar pattern of bioremoval capacity was detected for temperature which was 50 Cº giving capacities of 72.0 ± 0.0 mg Cr/l, 60.0 ± 1.84 mg Ni/l and 54.0 ± 1.72 mg Zn/l. In case of contact time, these capacities were again similar to those of pH and temperature and found to be 76.0 ± 3.0 mg/l , 64.0 ± 1.82 mg/l and 60.0 ± 2.0 mg/l for Cr, Ni, and Zn respectively but at 1 hour contact time.